'Silence is not always golden'. (27th April 2022) - Orthaber, Sara
Abstract : The past two decades have seen a growing interest in research on call centre discourse from sociolinguistic and pragmatic perspectives. Turn-by-turn micro-analyses of call centre interactions have looked at the complex power relations and face-considerations in dealing with customers' and agents' impolite behaviour. Although silence is ubiquitous in dyadic conversations, surprisingly few studies of call centre interactions have investigated silence between adjacency pairs and the potential trouble it may indicate. To fill this gap, this paper explores silence in service calls. Specifically, it first looks at routine calls for information and the most common ways in which silence is accounted for by the agents. It then examines non-routine calls where silence becomes interactionally meaningful following the agents' withheld responses at a transition-relevance place. Thus, silence becomes marked behaviour by virtue of being oriented to as unexpected by the customer and thus open to evaluations of impoliteness.